PENAFSIRAN SAB’ SAMAWAT DALAM KITAB TAFSIR AL-QUR’AN AL-AZIM KARYA IBNU KATSIR (KAJIAN INTERTEKSTUALITAS JULIA CRISTEVA) - FATIMAH FATMAWATI (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
This paper found that there is intertextuality in Ibn Kathir's Work, Al-Qur’an Al-Azim. When Ibn Katsir interpret Sab 'samawat in seven surahs, Qs. Al-Baqarah: 29, al-Isra ': 44, al-Mu'minun: 86, Fussilat: 12, at -Talaq: 12, al-Mulk: 3, and N h: 15, his  interpretation has a correlation with previous texts. Related interpretations contained in the Al-Jami 'Li Ahkam al-Qur'an by Qurthubi, Jami' al bayan an ta'wil ay al-Quran by Thabari , and Ibn Mas'ud's exegesis. Furthermore, Al-Qur'an's Al-Azim's work, as a phenotext, has a lot of similarity with The Book of Enoch, as its genotext. The similarity is found in three points. First, the sky consists of seven layers, some of which are above the others. Second, every sky inhabit by the angels. Third, the angels in first sky give an honour to second sky habitant, the angels in second sky give an honour to third sky habitant, and so on. So, this paper attest Kristeva's theory that there is no independent text, one text with another is always related. And the other hand, this paper prove al-Quran as a cultural product, muntaj as-Saqafi.